Genetic predisposition of the gastrointestinal microbiome and primary biliary cholangitis: a bi-directional, two-sample Mendelian randomization analysis - Luo, Xin; You, Xin (Frontiers in Endocrinology, 2023)
Background The gut-liver axis indicates a close relationship between the gastrointestinal microbiome (GM) and primary biliary cholangitis (PBC). However, the causality of this relationship remains unknown. This study investigates the causal relationship between the GM and PBC using a bidirectional, two-sample Mendelian randomization (MR) analysis. Methods Genome-wide association data for GM and PBC were obtained from public databases. The inverse-variance weighted method was the primary method used for MR analysis. Sensitivity analyses were conducted to assess the stability of the MR results. A reverse MR analysis was performed to investigate the possibility of reverse causality. Results Three bacterial taxa were found to be causally related to PBC. Class Coriobacteriia (odds ratio (OR) = 2.18, 95% confidence interval (CI): 1.295-3.661, P< 0.05) and order Coriobacteriales (OR = 2.18, 95% CI: 1.295-3.661, P<0.05) were associated with a higher risk of PBC. Class Deltaproteobacteria (OR = 0.52, 95% CI: 0.362–0.742, P< 0.05) had a protective effect on PBC. There was no evidence of reverse causality between PBC and the identified bacterial taxa. Conclusion Previously unrecognized taxa that may be involved in the pathogenesis of PBC were identified in this study, confirming the causality between the GM and PBC. These results provide novel microbial targets for the prevention and treatment of PBC.